Martinican Creole danse gestures and their african substrate : Lexicon, form, origin : globalizing approach essay - (:unkn) unknown (My University, 2024)
Martinican Creole dance gestures and their african substrate is a particularly difficult theme to study and understand. Indeed, it alone synthesizes nearly four centuries of colonization and syncretism at the anthropological level, because it draws on all the conscious or unconscious contributions of the different communities which have animated and kept martinican society alive. Even those who have disappeared have left traces in the gestural memory. When we are interested in this gesture and we deepen it, it reveals an african base and substrate which are, to say the least, common to all these contributions and which at the same time are at the basis of the process of creolization which is carried out over time. Nothing was completely lost. On the other hand, many initial aspects have been remodeled, integrated, transformed in this matrix transmitted orally and which only requires self-awareness to be assumed and developed.
Keywords: African Research